2011
DOI: 10.1016/j.jgo.2011.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in symptoms and their interference with quality of life in 903 cancer patients undergoing radiation therapy

Abstract: Structured Abstract Objectives To evaluate the relationship of age with symptoms and interference with daily function and QOL during RT. Design A prospective observational study. Setting A university-based radiation oncology department. Participants 903 cancer patients who received radiation therapy (RT). The mean age was 61 yrs (18-92) and 41% were ≥ 65 yrs. Measurements A symptom inventory was administered pre- and post-RT. Patients rated 10 symptoms and their interference with daily function and QO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 26 publications
5
47
0
1
Order By: Relevance
“…The most common symptoms reported in these surveys are consistent with what is known from the larger survivorship literature (Farley Short, Bradley, & Yabroff, 2009; Pachman, et al, 2012; Yabroff, Lund, Kepka, & Mariotto, 2011; B.J. Zebrack, 2011): more than half of the 2910 survivors who were included in these analyses reported fatigue (often the most common symptom reported by samples of survivors (e.g., (Barbera, et al, 2010; Becker, Rechis, Kang, & Brown, 2010; Mohile et al, 2011)), cognitive problems, fears of recurrence, problems with grief or identity, emotional distress, problems with body image, and, for those who were in school at their time of diagnosis, concerns about educational goals. The burden of physical, emotional, and practical concerns reported by survey respondents remained consistently high across the 2006 and 2010 surveys, with one exception: employment concerns were more commonly reported among respondents to the 2010 survey.…”
Section: Discussionsupporting
confidence: 79%
“…The most common symptoms reported in these surveys are consistent with what is known from the larger survivorship literature (Farley Short, Bradley, & Yabroff, 2009; Pachman, et al, 2012; Yabroff, Lund, Kepka, & Mariotto, 2011; B.J. Zebrack, 2011): more than half of the 2910 survivors who were included in these analyses reported fatigue (often the most common symptom reported by samples of survivors (e.g., (Barbera, et al, 2010; Becker, Rechis, Kang, & Brown, 2010; Mohile et al, 2011)), cognitive problems, fears of recurrence, problems with grief or identity, emotional distress, problems with body image, and, for those who were in school at their time of diagnosis, concerns about educational goals. The burden of physical, emotional, and practical concerns reported by survey respondents remained consistently high across the 2006 and 2010 surveys, with one exception: employment concerns were more commonly reported among respondents to the 2010 survey.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, increasing age is associated with the risk of multiple comorbidities, which in themselves could be predisposing, precipitating, or perpetuating risk factors for the development of sleep problems even more so than the cancer itself or its treatments 8384 in large studies, older age has rarely been identified as a risk factor for sleep problems and, in fact, younger cancer patients seem to be at higher risk for sleep problems than older cancer patients 7,85. It is unclear why younger patients are at risk for the development of sleep problems during treatment, but it is possible that disease severity, more aggressive treatments, and/or expectations for better health among younger patients are responsible for higher sleep problem rates 7…”
Section: Biological Mechanisms Contributing To Chemotherapy-associatementioning
confidence: 99%
“…In a study of oncology patients undergoing RT [15], sleep disturbance, pain, and distress were significantly less prevalent among older patients compared to younger patients, while shortness of breath was significantly more prevalent among older patients before RT. In another study of newly diagnosed cancer patients [16], age was weakly correlated with ratings of symptom distress ( r  = −0.11, p < 0.02) and older patients reported lower levels of symptom distress.…”
Section: Introductionmentioning
confidence: 99%